2014
DOI: 10.1016/j.pec.2013.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of the health consequences of obesity among overweight/obese Black and Hispanic adults

Abstract: Objective To measure knowledge of the health consequences of obesity among overweight/obese Black and Hispanic adults and examine the relationship to prior weight loss. Methods Knowledge of the health consequences of obesity was assessed among 410 Black and Hispanic adults with BMI ≥ 25 kg/m2 enrolled in a behavior change weight loss study. The relationship between obesity risk knowledge and previous weight loss was also examined. Results The majority of participants were knowledgeable of the risk of hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 21 publications
7
22
0
Order By: Relevance
“…As to the knowledge about the complications of obesity, the percentages of correct answers were close to those found in a research carried out in New York, which assessed the knowledge of overweight black and Hispanic adults about the consequences of obesity for health and identified that the majority knew about the risk of hypertension (94%), diabetes (96%), musculoskeletal pain and problems (89%), and sleep apnea (89.0%) (20) . A cross-sectional study carried out in Texas with 1,420 low-income women aged between 16 and 40 years, who intended to become pregnant, found that they did not know the health risks associated with obesity, which could put them at risk of developing diabetes or hypertension in the years before conception (21) .…”
Section: Discussionsupporting
confidence: 68%
“…As to the knowledge about the complications of obesity, the percentages of correct answers were close to those found in a research carried out in New York, which assessed the knowledge of overweight black and Hispanic adults about the consequences of obesity for health and identified that the majority knew about the risk of hypertension (94%), diabetes (96%), musculoskeletal pain and problems (89%), and sleep apnea (89.0%) (20) . A cross-sectional study carried out in Texas with 1,420 low-income women aged between 16 and 40 years, who intended to become pregnant, found that they did not know the health risks associated with obesity, which could put them at risk of developing diabetes or hypertension in the years before conception (21) .…”
Section: Discussionsupporting
confidence: 68%
“…They are less confident about their knowledge about the association of obesity and other aspects of general health. These findings are supported by previous research conducted by Winston et al [19] who reported increased knowledge of linkages of obesity with diabetes, blood pressure, cholesterol, and heart disease, and the lack of knowledge of the reproductive consequences found by Cardozo et al [5] and Cardozo et al [7]. Our results further show our participants' awareness of the association between obesity and health outcomes was not associated with ethnicity in contrast to previous studies where whites tend to be more knowledgeable on the effects of obesity compared to other ethnic groups [13].…”
Section: Discussionsupporting
confidence: 92%
“…Knowledge of the health consequences of different behaviors has historically been an important contributor to educational disparities in health behaviors. However, in today’s society, awareness of the consequences of smoking and obesity are near universal (Link 2008; Winston et al 2014), and thus, this type of knowledge appears inadequate to account for educational differences in these behaviors. Information and access to technology about ways to maintain health or become healthy may be more relevant for today’s health behavior disparities.…”
Section: Theoretical Frameworkmentioning
confidence: 99%